2014
DOI: 10.1002/ptr.5186
|View full text |Cite
|
Sign up to set email alerts
|

Gelidium elegans, an Edible Red Seaweed, and Hesperidin Inhibit Lipid Accumulation and Production of Reactive Oxygen Species and Reactive Nitrogen Species in 3T3‐L1 and RAW264.7 Cells

Abstract: Gelidium elegans is an edible red alga native to the intertidal area of northeastern Asia. We investigated the effect of G. elegans extract and its main flavonoids, rutin and hesperidin, on lipid accumulation and the production of reactive oxygen species (ROS) and reactive nitrogen species (RNS) in 3T3-L1 and RAW264.7 cells. Our data show that G. elegans extract decreased lipid accumulation and ROS/RNS production in a dose-dependent manner. The extract also inhibited the mRNA expression of adipogenic transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 45 publications
4
26
0
Order By: Relevance
“…Our previous study, as well as recent studies, suggested that GENS may exert a protective effect on adipogenesis in adipocytes in vitro [49] and in adipose tissue mass in vivo by regulating C/EBPα and PPARγ proteins [19]. Consistent with previous results, our results showed that GENS decreased the expression of C/EBPα and PPARγ in white adipose tissue in HFD-fed mice.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous study, as well as recent studies, suggested that GENS may exert a protective effect on adipogenesis in adipocytes in vitro [49] and in adipose tissue mass in vivo by regulating C/EBPα and PPARγ proteins [19]. Consistent with previous results, our results showed that GENS decreased the expression of C/EBPα and PPARγ in white adipose tissue in HFD-fed mice.…”
Section: Discussionsupporting
confidence: 92%
“…Jeon et al . indicated that hesperidin may interfere with lipid accumulation and a production of reactive oxygen species and reactive nitrogen species in mouse adipocyte‐like cells and macrophages . In accordance, two studies on rats reported protective effect of hesperidin against dimethylnitrosamine and carbon tetrachloride induced liver fibrosis by diminishing hepatic inflammation, oxidative stress and liver injury.…”
Section: Flavanones: Naringenin Hesperitinmentioning
confidence: 63%
“…Jeon et al also reported a significant reduction on the LPSinduced NO production in Gelidium elegans extracttreated RAW264.7 cells. G. elegans is an edible red alga native to the intertidal area of northeastern Asia, which contains rutin and hesperidin as its main flavonoids (Jeon et al, 2014). Interestingly, in a correlative analysis of the methanolic extracts of seven citrus fruit peels, Hsd was not designated as the key determinant in the inhibition of PGE2 and NO production when compared to polymethoxy flavones.…”
Section: Cellular Modelsmentioning
confidence: 99%